Organizational Agility as the Key to Business Sustainability: An Empirical Study on Digital Startups - Maheswari, Nadya Ramadhani; Santoro, Ardiansyah Pratama (Universitas Sains dan Teknologi Komputer, 2026)
Digital transformation compels Indonesian digital startups to remain agile in responding to rapid market and technological changes. The high failure rate among startups indicates that business sustainability cannot rely solely on technological innovation but must be supported by organizational agility—the ability to adapt quickly, innovate continuously, and manage dynamic environments effectively. This study aims to analyze the role of organizational agility in ensuring business sustainability among digital startups in Indonesia. Using a quantitative explanatory approach, web-based questionnaires were distributed to 200 startup managers across various digital sectors. Data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess the effects of four agility dimensions: structural flexibility, adaptability speed, innovation capability, and market responsiveness. The findings reveal that all agility dimensions significantly and positively affect business sustainability, with innovation capability emerging as the most influential factor. The R² value of 0.68 indicates that agility accounts for a substantial portion of the variance in the sustainability of digital startups. Theoretically, this study reinforces the dynamic capabilities framework by positioning agility as the core strategic link between internal transformation and external environmental changes. In practice, it suggests that startups should foster innovation, accelerate decision-making, and leverage these insights to shape policies that support a sustainable digital ecosystem.